Exploring Character of Pancasila Students in the English Textbook for the Tenth Grade Senior High School Students - Hadna Suryantari (English Language Education Department, Universitas Majalengka, 2022)
A textbook plays a significant role in teaching and learning process and is seen as a means to convey and strengthen character education. A textbook presents character education values through organized materials which can be utilized as a resource of learning experience. Moreover, it provides a useful choice in teaching and learning process which enables students to comprehend the character education building while they involve themselves during school years. This research examines Character of Pancasila Students which is presented in an English textbook published by the Ministry of Education and Culture of the Republic of Indonesia for grade 10. Type of research is content analysis research. The source of the data for this research is the English textbook for 10th grade students. Based on the result of the analysis in the English textbook, all Character of Pancasila Students dimensions are implemented thus the English textbook is appropriate as teaching material which develops Character of Pancasila Students values of tenth grade senior high school students Keyword: character education, independent learning curriculum, character of pancasila students, English Textbook, tenth grade students